Theoretical study of conformational transition of CDK4 by association of cyclin D3. (2nd September 2019) - Kawaguchi, Kazutomo; Arwansyah, Muhammad Saleh; Kataoka, Tatsuki; Nagao, Hidemi
ABSTRACT: We present coarse-grained simulations to investigate folding and association of cyclin-dependent kinase 4 (CDK4) with cyclin D3. In our simulations, the Gō-like model and our coarse-grained model are applied to describe intramolecular and intermolecular interaction of protein molecules, respectively. We investigate conformational stability of each state of CDK4 with/without association to cyclin D3 on a single basin potential with reference to each state of CDK4. The results of simulations for the native CDK4 with cyclin D3 are consistent with an experimental observation. The open CDK4 may associate to cyclin D3 on a different interface from cyclin D3-native CDK4 complex structure. If the open CDK4 associates to cyclin D3, the open CDK4 can slightly fold and become smaller, suggesting an unfolded intermediate. After a double-basin potential with reference to the native and open states of CDK4 is given, the open CDK4 associated with cyclin D3 can smoothly shift to the native CDK4. We propose a structure of a potential candidate of an unfolded intermediate during activation of CDK4. GRAPHICAL ABSTRACT: